A (pentafluoroethyl)(trifluoromethyl)carbene complex of iridium and reductive activation of its sp3 α, β, and γ carbon–fluorine bonds to give perfluoro-2-butyne, perfluoro-1, 2, 3-butatriene and perfluoro-1-irida-2-methyl-2-cyclobutene) complexes. Issue 45 (9th July 2015) - Yuan, Jian; Hughes, Russell P.; Rheingold, Arnold L.
Abstract : Inner-sphere reduction of a (pentafluoroethyl)(trifluoromethyl)carbene ligand affords perfluorobutyne, perfluorobutatriene and perfluorometallacyclobutene ligands. Abstract : The (pentafluoroethyl)(trifluoromethyl)carbene complex Cp*Ir(CO)[C(CF3 )(C2 F5 )] was synthesized by the reductive activation of the α-C–F bond in the perfluoro- sec -butyl-iridium complex Cp*Ir(CO)[CF(CF3 )(C2 F5 )](I) with Na/Pb alloy. This compound exists as two geometric isomers in solution; the structure of one isomer has been determined by a single crystal X-ray diffraction study and contains two independent molecules in the asymmetric unit. Further reduction of this carbene complex with Na/Pb alloy afforded the perfluoro-2-butyne iridium complex Cp*Ir(CO)(η 2 -CF3 CCCF3 ) by an overall 2-electron reduction and elimination of two β-fluorides. When magnesium graphite was utilized as the reducing agent for the further reduction, Cp*Ir(CO)(η 2 -CF3 CCCF3 ) was produced as a minor product and the major product was the perfluoroiridacyclobutene complex Cp*Ir(CO)(η 2, 4 -CF3 CCFCF2 ) resulting from a γ-C–F bond activation. Direct reduction of the precursor Cp*Ir(CO)[CF(CF3 )(C2 F5 )](i ) with magnesium graphite generated the tetrafluorobutatriene iridium complex Cp*Ir(CO)(η 2, 3 -CF2 CCCF2 ) along with the perfluoro-2-butyne complex and perfluoroiridacyclobutene complexes in a ratio of 1 : 2 : 6. These reductive inner-sphere pathways to unsaturated fluorocarbon ligands illustrate that carbon–fluorine bond activation can take place at α-, β- and γ-carbons but that selectivity in these heterogeneous reductions is difficult to control, with a variety of fluoride eliminations possible for complex perfluoroalkyl ligands. Density Functional Theory (DFT/B3LYP-D3/LACV3P**++) is used to explore the relative energetics of products and intermediates in these reactions.